Incident Non-AIDS Comorbidity Burden Among Women With or at Risk for Human Immunodeficiency Virus in the United States. (3rd January 2021) - Collins, Lauren F; Sheth, Anandi N; Mehta, C Christina; Naggie, Susanna; Golub, Elizabeth T; Anastos, Kathryn; French, Audrey L; Kassaye, Seble; Taylor, Tonya N; Fischl, Margaret A; Adimora, Adaora A; Kempf, Mirjam-Colette; et al.
Abstract: Background: Human immunodeficiency virus (HIV) infection may accelerate development of aging-related non-AIDS comorbidities (NACMs). The incidence of NACMs is poorly characterized among women living with HIV (WLWH). Methods: WLWH and HIV-seronegative participants followed in the Women's Interagency HIV Study (WIHS) through 2009 (when >80% of WLWH used antiretroviral therapy) or onward were included, with outcomes measured through 31 March 2018. Sociodemographics, clinical covariates, and prevalent NACM were determined at enrollment. We used Poisson regression models to determine incident NACM burden (number of NACMs accrued through most recent WIHS visit out of 10 total NACMs assessed) by HIV serostatus and age. Results: There were 3129 participants (2239 WLWH, 890 HIV seronegative) with 36 589 person-years of follow-up. At enrollment, median age was 37 years, 65% were black, and 47% currently smoked. In fully adjusted analyses, WLWH had a higher incident NACM rate compared with HIV-seronegative women (incidence rate ratio, 1.36 [95% confidence interval (CI), 1.02–1.81]). Incident NACM burden was higher among WLWH vs HIV-seronegative women in most age strata (HIV × age interaction: P  = .0438), and women <25 years old had the greatest incidence rate ratio by HIV serostatus at 1.48 (95% CI, 1.19–1.84) compared with those in older age groups. Incident NACM burden was associated with traditional comorbidity risk factors but not HIV-specific indices. Conclusions: Incident NACM burden was higher among WLWH than HIV-seronegative women. This difference was most dramatic among women aged <25 years, a group for whom routine comorbidity screening is not prioritized. Established non-HIV comorbidity risk factors were significantly associated with incident NACM burden. More data are needed to inform best practices for NACM screening, prevention, and management among WLWH, particularly young women. Abstract : Among women in the United States, the burden of incident non-AIDS comorbidities was higher for those living with human immunodeficiency virus (HIV) compared with those without HIV, and this difference was greatest for young women, a group not prioritized in routine comorbidity screening.